A Review of Game-Based Learning in Higher Education: Exploring Escape-Room Methodologies in Educational Settings - Janet Tan, Sui Ling; Binti Suhaili, Intan Nurul Annisha; Binti Adnan, Siti Nur Maisarah; Binti A Ham Suri, Nor Syahira; Bin Ahmad Zaky, Ahmad Nabil Mukhlis (Indian Journal of Pharmaceutical Education and Research, 2026)
ABSTRACT Conventional teaching approaches that lack interactive techniques may hinder the effectiveness of knowledge acquisition and student engagement. Innovative teaching approaches are essential to engage with tech-savvy Generation Z students. Game-based concepts, particularly educational escape rooms are gaining attention as effective teaching tools in higher education. This review explores the development and implications of educational escape rooms in terms of student knowledge, engagement, problem-solving skills, and teamwork. Studies showed that it is evident that educational escape rooms exhibit positive impacts towards the students’ learning, attributed to increased motivation, satisfaction, and peer learning. Notably, escape rooms facilitate a shift from traditional didactic methods to more interactive and immersive learning experiences. Despite the promising outcomes, further research is necessary to further refine the design and maximise the impact of the educational escape room. This review provides valuable insights for educators and researchers, highlighting the potential of educational escape rooms to transform higher education and suggesting directions for future research.
Keywords: Active Learning; Educational Games; Game-Based Learning; Higher Education.